Constructing unverifiable reality: a qualitative study of the prison planet conspiracy hypothesis on YouTube - Barzen, Annika (Frontiers in Sociology, 2025)
IntroductionThis study examines the construction of unverifiable realities through the analysis of a YouTube video and its associated comments on the Prison Planet theory, a spiritual and non-falsifiable conspiracy hypothesis. It investigates how digital interactions contribute to the legitimization of alternative epistemic frameworks.MethodsUsing Grounded Theory, the research analyzes the transcript of a 54-min YouTube video along with 450 viewer comments. The study focuses on how credibility is constructed through the interplay between video content and audience engagement.ResultsThe credibility of the unverifiable Prison Planet theory is constructed through a collective epistemic authority, reinforced by an emotionally engaged community. This authority emerges from the content creator’s perceived trustworthiness and emotional appeal, as well as the creation of existential meaning. The community further validates this knowledge, collectively reinforcing the theory’s credibility despite its lack of verifiability.DiscussionThe results highlight the significance of social interactions and emotional resonance in shaping knowledge formation. The study discusses the role of epistemic uncertainties and collective identity processes in digital communities, as well as the dual function of digital platforms as spaces for meaning-making and commercialization.ConclusionThis study highlights the construction of a collective epistemic authority, which is established through an emotionally engaged community. It shows how digital platforms facilitate the legitimization of unverifiable knowledge by fostering trust and validation among users. This research contributes to understanding the mechanisms behind the social construction of conspiracy theories in the digital age.